Gender Communication Difference Between Students in Online Learning - Putra, I Gede Putu Dharma Dewangga (The Art of Teaching English as a Foreign Language (TATEFL), 2022)
This study was focused on exploring the communication difference between male and female students during the online learning. The study was conducted by employing mixed method as the method of the research. This study was conducted at one vocational school in one vocational school at Tabanan regency, Bali. The researcher used Google Form order to obtain the data from the sample of the research. The data gathering was implemented virtually due to the pandemic of Covid-19. The researcher was using WhatsApp to send the online survey the sample of the research. During the online learning, there were any differences between the male and female students in terms of communication. The data showed interesting data that showed the differences between male and female students in terms of language politeness during the communication.